(untitled) (Eurasian Journal of Engineering and Technology, 2022)
This work presents a systematic review of the latest studies on the promotion of smart poultry based on modern and smart technologies in line with the development of the agricultural sector, such as artificial intelligence, and the Internet of Things that are used to cover issues in poultry. Then, the classification was created to group the articles according to their motivations, goals, and challenges. The search was performed in three major databases: IEEE Xplore, Science Direct, and Scopus. A total of 995 research papers were collected from 2016 to 2022. The retrieved articles were filtered and 52 articles were selected and categorized into three categories. System monitoring falls under the first category (n=39/52; 75%) and may be used to monitor the environment to maintain ideal environmental conditions, monitor chickens to find illnesses and determine chicken mortality, or monitor chicken weight. Monitoring based on the dataset, which keeps data in the cloud and analyzes it to detect illnesses and take necessary action, is included in the second category (n=2/52; 3.85%). Other is the third group (n=11/52; 21.15%). On the other hand, it must take some limitations in such applications more seriously, for example: the establishment of a system adapting to the appropriate conditions of the chicken according to the age of the chicken and attention to factors that reduce thermal stress that increase productivity. Our study attempts to provide a comprehensive overview of intelligent poultry in the literature. We hope that other researchers will use this study as a starting point to expand the research further based on the challenges we have discussed